Impact of Tramadol Administration on Cardio-Electrophysiological Balance following General Surgery - Adnan, Muhammad Abdullah; Rehman, Syeda Mahnoor; Khan, Muhammad; Ansari, Ayeshe; Ansari, Najm Us Saqib (Biological and Clinical Sciences Research Journal, 2025)
Tramadol is widely used for perioperative analgesia but has been implicated in electrophysiological effects on ventricular repolarisation and conduction. The index of cardiac electrophysiological balance (ICEB = QT/QRS) and its corrected form (ICEBc = QTc/QRS) are emerging ECG-derived markers linked to pro-arrhythmic risk. Evidence on tramadol's impact on these indices in surgical patients is limited. Objective: To assess the effect of intravenous tramadol on ICEB and ICEBc in adults undergoing general surgery. Methods: This prospective, single-centre, pre–post observational study was conducted in the General Surgery Department of Ibn-e-Siena Hospital, Multan, from June 2024 to June 2025. We enrolled 100 consecutive adults undergoing general surgery. All patients received intravenous tramadol 2 mg/kg. Standardized 12-lead ECGs were obtained immediately before and after tramadol administration to measure QT, QTc, and QRS; ICEB was calculated as QT/QRS and ICEBc as QTc/QRS. Vital signs (blood pressure, heart rate, oxygen saturation) were monitored throughout. Percentage change from baseline was computed for each parameter. Descriptive statistics summarized data; pre–post differences were tested using two-sided paired tests with α=0.05. Linear regression explored the association between tramadol dose (total mg, reflecting weight-based dosing) and post-dose ICEBc, adjusting for the corresponding baseline value. Results: Heart rate changed by 0.5% from baseline. QT and QTc increased by 2.5% (both p<0.001). QRS duration decreased by 4.5% after tramadol. ICEB and ICEBc increased by 3.6% and 3.3%, respectively. In regression analysis, tramadol dose independently predicted higher corrected ICEB (β=0.198, p=0.005). No deaths or serious arrhythmias were observed during follow-up. Conclusion: Intravenous tramadol is associated with statistically significant, directionally pro-arrhythmic shifts in ECG-derived indices of electrophysiological balance (increased ICEB/ICEBc) in general-surgery patients, although no serious arrhythmias occurred. Peri-operative monitoring of repolarization and conduction parameters may be prudent when tramadol is used, particularly at higher weight-based doses.